Influence of Profitability, Solvability, and Company Growth on Going Concern Audit Opinions - Endah Satriani; Yulis Alfia (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2020)
This study aims to determine the effect of profitability, solvency and company growth on going concern audit opinion. The object of this research is mining companies listed on the Indonesia Stock Exchange in 2016 - 2018. The sample selection in this study using purposive sampling. The data analysis used is logistic regression with statistical test tools used is SPSS 25. The results of this study indicate that simultaneously the variables of profitability, solvency, and company growth have an effect on going concern audit opinion. The partial results of the research are profitability has a significant negative effect on going concern audit opinion, the solvency has a significant positive effect on going concern audit opinion, while the company growth variable has no effect on going concern audit opinion.